SOIL EVOLUTION AFTER FIRE IN QUERCUS-ILEX AND PINUS-HALEPENSIS FORESTS - FERRAN, A.; SERRASOLSAS, I.; Vallejo, V. R. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Four contrasted burned sites in Catalonia (NE Spain) have been compared to-illustrate the diversified response to fire depending on the interaction of substrate-vegetation characteristics. Data from plant cover evolution, forest floor layers and soil chemical properties demonstrated that the garrigue on limestone is the most resilient ecosystem as a result of the resprouting capacity of Ouercus coccifera and the high soil stability. The shrubland on marls was however, the least resilient, with the poorest plant regeneration and greatest erosion rates. The plant communities on conglomerates and the holm oak forest on schists, represented intermediate situations, where the variable degree of erosion and nutrient losses were compensated by a rapid plant colonization just after the fire.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: burned sites; ecosystem resilience; fire; Quercus coccifera; Quercus ilex; Shrubland; Spain

STRUCTURE OF MIXED HOLM-OAK (QUERCUS-ILEX) ALEPPO PINE (PINUS-HALEPENSIS) FORESTS IN NORTHEASTERN SPAIN - Espelta, J. M.; GENE, C.; Retana, J.; TERRADAS, J. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Mixed forests of Aleppo pine (Pinus halepensis) and holm-oak (Quercus ilex) cover a great part of Northeastern Spain. Nevertheless, little is known about their structure, dynamics and regeneration. For some years, a research group in CREAF has collected data about those aspects, in order to use them to develop models that could be used as a tool for forest management. Previous results obteined about the structure of these stands are presented in the present paper.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: mixed forests; Pinus halepensis; Quercus ilex; Spain